PENGARUH MEDIA COUNTING BOX TERHADAP KEMAMPUAN BERHITUNG DI TAMAN KANAK-KANAK - Haura Al Khairi; Serli Marlina (STKIP Subang, 2026)
This study examines the influence of counting box media on children's arithmetic skills, especially those aged 5-6 years. The method used is a quantitative, quasi-experimental design with 30 children, comprising an experimental class and a control class. Data collection and analysis use the SPSS application version 31 for Windows, which includes normality tests and nonparametric tests (Mann-Whitney and Wilcoxon). The results obtained indicate a significant influence given by counting box media on children's abilities, with a value of 0.001 < 0.05. Therefore, counting box media can be used as an effective learning media idea in supporting the development of children's arithmetic skills.